Menakar Partisipasi Politik Mahasiswa Berbasis Pembelajaran (Studi Eksperimen pada Mahasiswa Jurusan Ilmu Komunikasi Universitas Sriwijaya) - Elfandari, Safitri; Ilham, Muhamad Hidayatul; Lionardo, Andries (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2023)
Abstract. Students as agents of change and first-time voters have an important role in the sustainability of politics in Indonesia. Students are expected to be able to bring about changes in the sustainability of Indonesian democracy of general election in 2024. Political communication courses are introduced to students of Communication Science at FISIP Sriwijaya University. The importance of participating, responding, and knowing the scope, as well as the definition of a form of political communication strategy. By introducing political communication, it is expected that they will be able to think comprehensively and critically in the context of political communication. This course does not only provide political communication theory but also provides an experimental space for students to participate in political communication practice. starting from party logos, ideology, vision, and mission, strategies, and campaigns and voting through social media Instagram. This research is descriptive qualitative in nature, using observation techniques, interviews and documentation to obtain the necessary information and data. The results showed that communication science students at the Faculty of Social and Political Sciences at Sriwijaya University were able to practice political communication and have an interest in the dynamics of political communication in Indonesia. By simulation they have an experience about political communication, starting from introducing their political parties, logos, vision and mission, strategies and conducting campaigns to voting through Instagram social media. And this can reduce the apathy of the younger generation towards politics in Indonesia.